A Comparison of Nonoperative and Operative Treatment of Type 2 Tibial Spine Fractures. Issue 1 (21st January 2021) - ; Prasad, Niyathi; Aoyama, Julien T.; Ganley, Theodore J.; Ellis, Henry B.; Mistovich, R. Justin; Yen, Yi-Meng; Fabricant, Peter D.; Green, Daniel W.; Cruz, Aristides I.; McKay, Scott; Kushare, Indranil; et al.
Background: Tibial spine fractures (TSFs) are typically treated nonoperatively when nondisplaced and operatively when completely displaced. However, it is unclear whether displaced but hinged (type 2) TSFs should be treated operatively or nonoperatively. Purpose: To compare operative versus nonoperative treatment of type 2 TSFs in terms of overall complication rate, ligamentous laxity, knee range of motion, and rate of subsequent operation. Study Design: Cohort study; Level of evidence, 3. Methods: We reviewed 164 type 2 TSFs in patients aged 6 to 16 years treated between January 1, 2000, and January 31, 2019. Excluded were patients with previous TSFs, anterior cruciate ligament (ACL) injury, femoral or tibial fractures, or grade 2 or 3 injury of the collateral ligaments or posterior cruciate ligament. Patients were placed according to treatment into the operative group (n = 123) or nonoperative group (n = 41). The only patient characteristic that differed between groups was body mass index (22 [nonoperative] vs 20 [operative]; P = .02). Duration of follow-up was longer in the operative versus the nonoperative group (11 vs 6.9 months). At final follow-up, 74% of all patients had recorded laxity examinations. Results: At final follow-up, the nonoperative group had more ACL laxity than did the operative group ( P < .01). Groups did not differ significantly in overall complication rate, reoperation rate, or total range of motion (all, P > .05). The nonoperative group had a higher rate of subsequent new TSFs and ACL injuries requiring surgery (4.9%) when compared with the operative group (0%; P = .01). The operative group had a higher rate of arthrofibrosis (8.9%) than did the nonoperative group (0%; P = .047). Reoperation was most common for hardware removal (14%), lysis of adhesions (6.5%), and manipulation under anesthesia (6.5%). Conclusion: Although complication rates were similar between nonoperatively and operatively treated type 2 TSFs, patients treated nonoperatively had higher rates of residual laxity and subsequent tibial spine and ACL surgery, whereas patients treated operatively had a higher rate of arthrofibrosis. These findings should be considered when treating patients with type 2 TSF.